2017
DOI: 10.7860/jcdr/2017/29065.10624
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Aphthous Stomatitis: An Assessment of Antioxidant Levels in Plasma and Saliva

Abstract: Introduction: Recurrent Aphthous Stomatitis (RAS) is a common oral mucosal disorder that affects 20% of the population worldwide. Factors such as trauma, stress, genetic, hypersensitivity, nutrition, immune disturbance and hormonal imbalance may disturb the oxidant and antioxidant balance of an organism and precipitate RAS, but the relationships are poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…SOD protects the cell from damage instigated by superoxide (O 2 − ) and hydroxyl radical, release H 2 O 2 in the process. Whereas SOD drops the steady-state level of O 2 − , catalase and peroxidases do the same for H 2 O 2 (Jesija, 2017).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…SOD protects the cell from damage instigated by superoxide (O 2 − ) and hydroxyl radical, release H 2 O 2 in the process. Whereas SOD drops the steady-state level of O 2 − , catalase and peroxidases do the same for H 2 O 2 (Jesija, 2017).…”
Section: Resultsmentioning
confidence: 94%
“…This activity can be attributed to a donation of hydrogen, to an electron reduction or direct scavenger effects. During the detoxi ication of increased H 2 O 2 by glutathione, consumption of chemically abridged GSH also rises (Jesija, 2017). Reka and Anuradha (2011) stated that tissue GSH levels are considerably abridged by oxidative stress and proposed that antioxidant defense impairment mechanisms could permit enhanced free radical prompted tissue damage.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Gupta et al found a marked reduction of UA levels in the serum of OLP patients in comparison with controls (4.058 ± 1.31 vs. 5.28 ± 0.961 mg/dL) [35]. By contrast, an increased level of salivary UA has been observed in the majority of generalized pathologic conditions such as diabetes and cardiovascular disorders, which might explain the systemic oxidative stress [3638], as opposed to changes of local nature. The increase in UA levels in these studies may constitute a compensatory antioxidative defense system of the entire human body aimed at preventing generalized oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent aphthous stomatitis (RAS) is a common oral mucosa disorder that affects 20% of the population (14). The clinical features of RSA are recurrent attack and shallow, rounded, discrete, painful oral ulcers (15).…”
Section: Salivary Antioxidants and Recurrent Aphthous Stomatitismentioning
confidence: 99%